PELATIHAN DAN MOTIVASI PENGARUHNYA TERHADAP KINERJA PERAWAT INSTALASI BEDAH SENTRAL RSUP SANGLAH DENPASAR DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING - Paramarta, Wayan Arya; Kasih, I Gusti Ayu Putri (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
The aims of this study was to explain the effect of training and motivation on employee engagement and the performance of nurses at the Sanglah Central Hospital of Denpasar. The type of data used in this study is qualitative and quantitative data, with data sources namely primary and secondary data. Data collection method is carried out by distributing questionnaires to respondents, while data analysis techniques used are path analysis techniques. The results of this study showed that training had an significant effect on employee engagement, motivation had an significant effect on employee engagement, training had an significant effect on performance, motivation had an significant effect on performance, employee engagement had an significant effect on performance, and training had an significant effect on performance through employee engagement, and motivation had an significant effect on performance through employee engagement nurses Sanglah Hospital Central Surgery Installation Denpasar.